Opinions of South Carolina Dental Students toward Tobacco Use Interventions - Gabrielle F. Cannick, BS; Alice M. Horowitz, PhD; Susan G. Reed, DDS, DrPH; (Blackwell Synergy, 2006)
Tobacco use accounts for 75 percent of oral cancer deaths in the United States. One objective of Healthy People 2010 is to increase the percentage of dentists who provide smoking cessation counseling. However, studies of dentists have shown that the majority feel inadequately prepared to do so.